Ginkgo biloba as an adjunct to methylphenidate in the treatment of attention deficit hyperactivity disorder in children: review of articles - Paria Hebrani; Fatemeh Behdani; Hoda Jalayer (Reviews in Clinical Medicine, 2015)
Attention-deficit/hyperactivity disorder is one of the most common psychiatric disorders in childhood. The medications which inhibit the reuptake of noradrenline and dopamine including psychostimulants such as methylphenidate and dextroamphetamine and non-stimulating pre-frontal cortex noradrenaline reuptake inhibitor such as atomoxetine, are the standard treatment of ADHD. Adverse effects of stimulants have been reported in thirty percent of patients with attention-deficit/hyperactivity disorder. More than fifty percent of the parents of these children have tried one or more complementary or alternative medicines including vitamins in their children. Ginkgo biloba has been described to be effective for various neuropsychiatric symptoms. It was assumed that ginkgo biloba might improve some symptoms of attention deficit disorder as well. Nevertheless, no systematic study reported a possible efficacy of ginkgo biloba in attention deficit disorder. This review article evaluates the available evidence on the efficacy of ginkgo biloba medication in Attention-deficit/hyperactivity disorder children to present an appropriate guidance for this common child disorder.